Physician experience improves ability to predict 6-month functional outcome of severe traumatic brain injury - Bernard, Rémy; Manzi, Elsa; Jacquens, Alice; Jurcisin, Igor; Chousterman, Benjamin; Figueiredo, Samy; Mathon, Bertrand; Degos, Vincent (Acta neurochirurgica, 2023)
Background The functional prognosis of severe traumatic brain injury (TBI) during the acute phase is often poor and uncertain. We aimed to quantify the elements that shade the degree of uncertainty in prognostic determination of TBI and to better understand the role of clinical experience in prognostic quality. Methods This was an observational, prospective, multicenter study. The medical records of 16 patients with moderate or severe TBI in 2020 were randomly drawn from a previous study and submitted to two groups of physicians: senior and junior. The senior physician group had graduated from a critical care fellowship, and the junior physician group had at least 3 years of anesthesia and critical care residency. They were asked for each patient, based on the reading of clinical data and CT images of the first 24 h, to determine the probability of an unfavorable outcome (Glasgow Outcome Scale < 4) at 6 months between 0 and 100, and their level of confidence. These estimations were compared with the actual evolution. Results Eighteen senior physicians and 18 junior physicians in 4 neuro-intensive care units were included in 2021. We observed that senior physicians performed better than junior physicians, with 73% (95% confidence interval (CI) 65–79) and 62% (95% CI 56–67) correct predictions, respectively, in the senior and junior groups ( p = 0.006). The risk factors for incorrect prediction were junior group (OR 1.71, 95% CI 1.15–2.55), low confidence in the estimation (OR 1.76, 95% CI 1.18–2.63), and low level of agreement on prediction between senior physicians (OR 6.78, 95% CI 3.45–13.35). Conclusions Determining functional prognosis in the acute phase of severe TBI involves uncertainty. This uncertainty should be modulated by the experience and confidence of the physician, and especially on the degree of agreement between physicians.